Tibial cortical lesions: A multimodality pictorial review. Issue 1 (January 2015) - Tyler, P.A.; Mohaghegh, P.; Foley, J.; Isaac, A.; Zavareh, A.; Thorning, C.; Kirwadi, A.; Pressney, I.; Amary, F.; Rajeswaran, G.
Highlights: Multimodality imaging plays an important role in the investigation and diagnosis of shin pain. We review the multimodality imaging findings of common cortically based tibial lesions. We also describe the rarer pathologies of tibial cortical lesions. Abstract: Shin pain is a common complaint, particularly in young and active patients, with a wide range of potential diagnoses and resulting implications. We review the natural history and multimodality imaging findings of the more common causes of cortically-based tibial lesions, as well as the rarer pathologies less frequently encountered in a general radiology department.